The financial trilemma and cross-border bank crisis management in ASEAN - Kun-Amornpong, Wassamon (2023)
Dirk Schoenmaker proposed a famous model of the financial trilemma, which states that three main policy objectives could not be achieved simultaneously: financial stability, financial integration, and national financial policies. Only two out of these three goals can go hand in hand. The dissertation tests the hypothesis taken from the financial trilemma model in the context of cross-border bank crisis management in Southeast Asia. It finds that an increase in financial integration in this sub-region due to the policies manifested from the Association of Southeast Asian Nations (ASEAN) as well as other factors could bring in benefits to Member States. Nevertheless, a higher level of financial integration potentially has downside effects when Member States follow policies which protect their national interest. The dissertation examines the solution to the financial trilemma as discussed by Schoenmaker, namely, the use of hard law to enhance integration and centralise power to the supranational level. It argues that in the case of Southeast Asia, the rule of law has not taken a firm root; for example, the ‘ASEAN Way’ is still a dominant norm in managing affairs in this sub-region. Idiosyncratic factors of ASEAN and Member States relevant to cross-border bank crisis management are discussed throughout the dissertation, in four main areas: bank supervision, bank resolution, deposit insurance, and bank crisis management. Moreover, the dissertation argues that the utilisation of soft laws, memoranda of understanding (MOUs) and government networks might be more promising than that of hard law in facilitating cross-border bank crisis management in ASEAN. The experience of the European Union (EU) has shown that a hard-law approach is not necessarily effective if the utilising system is not well-designed. Keywords: The Financial Trilemma, ASEAN, Bank Supervision, Bank Resolution, Deposit Insurance, Bank Crisis Management, the Rule of Law